Salientar a importância da adoção de bons hábitos alimentares por responsáveis de crianças na primeira infância - FERREIRA, Bianca Soares; SOUZA, Gabriela de Almeida; BRAIDO, Hermione Krystine Menezes (104, 2024)
Antes da idade pré-escolar, os padrões alimentares das crianças são formados e precisam ser ajustados ao longo do tempo. Este período é crucial para incentivar hábitos alimentares saudáveis, pois as crianças dependem dos adultos para aprender os princípios de uma alimentação equilibrada. Atualmente, observa-se um aumento no número de crianças com hábitos alimentares inadequados, o que resulta em sérios problemas de saúde, como sobrepeso, hipertensão e dificuldades no desenvolvimento físico e cognitivo. A responsabilidade dos pais é fundamental, já que seus próprios hábitos alimentares influenciam diretamente a dieta dos filhos. Além disso, o ambiente escolar também desempenha um papel importante na formação desses hábitos, pois é onde as crianças passam grande parte do tempo. O projeto tem como objetivo analisar a influência dos hábitos alimentares dos pais nas crianças de 2 a 3 anos, oferecendo orientações para apoiar os responsáveis nesse processo. A intenção é aumentar a conscientização dos pais sobre a importância de uma alimentação equilibrada e os impactos que seus hábitos têm na saúde de seus filhos. Desafios como a resistência a mudanças nos hábitos alimentares e a dificuldade de acesso a alimentos saudáveis, mas o projeto busca superar esses obstáculos. A meta é formar uma geração mais consciente e saudável, reduzindo os riscos de doenças crônicas no futuro, e promover mudanças significativas que durem por toda a vida.

Before preschool age, children's eating patterns are established and need to be adjusted over time . This period is crucial for fostering healthy eating habits, as children rely on adults to learn the principles of a balanced diet. Currently, there is a rising trend of children with poor eating habits, leading to serious health issues such Before preschool age, children's eating patterns are established and need to be adjusted over time. This period is crucial for fostering healthy eating habits, as children rely on adults to learn the principles of a balanced diet. Currently, there is a rising trend of children with poor eating habits, leading to serious health issues such as overweight, hypertension, and developmental delays. Parental responsibility is paramount, as their own dietary habits directly influence their children's eating patterns. Additionally, the school environment plays a significant role in shaping these habits, as children spend a considerable amount of time there.This project aims to analyze the influence of parental eating habits on children aged 2 to 3 years and provide guidance to support parents in this process. The goal is to raise parental awareness of the importance of a balanced diet and the impact their habits have on their children's health. Challenges such as resistance to dietary changes and limited access to affordable healthy foods may arise, but the project seeks to overcome these obstacles. The objective is to cultivate a more conscious and healthy generation, reducing the risk of chronic diseases in the future and promoting lasting lifestyle changes. as overweight, hypertension, and developmental delays. Parental responsibility is paramount, as their own dietary habits directly influence their children's eating patterns. Additionally, the school environment plays a significant role in shaping these habits, as children spend a considerable amount of time there.This project aims to analyze the influence of parental eating habits on children aged 2 to 3 years and provide guidance to support parents in this process. The goal is to raise parental awareness of the importance of a balanced diet and the impact their habits have on their children's health. Challenges such as resistance to dietary changes and limited access to affordable healthy foods may arise, but the project seeks to overcome these obstacles. The objective is to cultivate a more conscious and healthy generation, reducing the risk of chronic diseases in the future and promoting lasting lifestyle changes.
Highlight the importance of adopting good eating habits by those responsible for children in early childhood
Keywords: Alimentação escolar; Alimentação infantil; Hábitos alimentares; Família; Ambiente e Saúde